História de outrora contadas agora: formas identitárias profissionais e sociais de uma professora rural - Cruz, Daniela Cezar (2011)
This research is linked to the Research Line 1 - titled Training, Knowledge and Professional Development Program of Postgraduate, of the Federal University of Santa Maria (PPGE/UFSM), and focuses the life History of a teacher with 26 years in class in rural education. The general objective is "to investigate and analyze how is/was the professional and social identity of a teacher of rural education" of the municipality of Dilermando de Aguiar, RS. The methodology for this research is qualitative, using an approach biographical life History. The procedures were for the production of defined information starting from the reports autobiographical orals, written and photo analysis. In their methodological aspects, seek closer with the studies on life history and autobiography, memory and remembrance, social and professional Identity, literacy and rural education, from instruments of collections of information, appeared the following categories of analysis: rural education, literacy in rural education and social and professional identities. The autobiographies are an asset to education, in the measure in that enable greater visibility for the teacher. In this sense turns attention to the teacher's training course, and in his individuality as a story. The singularity of the life history is important, because makes it unique and special. The final considerations emphasize that identity is a dynamic process and, in this way, the teacher Tereza was building her identity within the family, social and professional in a rural community. These ones, in turn, are marked by the pedagogic autonomy, by creativity of the educational proposals, looking for a positive image of the profession and for an intensive professional responsibility, being constructed in his career.